Analisis Pengaruh Jumlah Load Cell Timbangan Jembatan Elektronik pada Pengujian Eksentrisitas sesuai Rekomendasi OIML R76 - Faradhiba Alifiyah Safitri; Danang Erwanto; Dian Efytra Yuliana (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
An electronic weighbridge are used to measure the mass of vehicles and their loads with electronic indicator. Weighbridge works using a strain gauge-based load cell connected in a wheatstone bridge configuration, where changes in resistance due to heavy forces will result in an output voltage that is sent to junction box to be displayed on indicator. Measurement accuracy is critical for weighbridge. One of the tests is eccentricity, which refers to weighbridge's ability to provide consistent measurement results even when the load is placed in different positions. This study aims to analyze the effect of number of load cells on results of eccentricity tests on electronic weighbridges based on the OIML R76 recommendation. The research was conducted on two weighbridges with identical specifications (16 m x 3 m platform, maximum capacity 60,000 kg, and readability 10 kg) but with different numbers of load cells. Weighbridge A uses 8 load cells, while Weighbridge B uses 6 load cells. The test points were determined by dividing platform into three sections, representing front, middle, and rear positions. Testing was performed using a truck as a ballast with a capacity of 21.520 kg. The results showed that Weighbridge A had an average error value of +0.33 kg, the largest error recorded at +2 kg at point 3. Meanwhile, Weighbridge B had an average error value of +3.17 kg, with the largest error recorded at -9 kg at point 3. It can be concluded that Weighbridge A provides more accurate measurement results than Weighbridge B. This is because Weighbridge A, with more load cells, achieves more even load distribution, particularly when weighing in both directions. In contrast, Weighbridge B demonstrated better accuracy for single-direction weighing but experienced greater errors when the load was tested in rolling positon, due to uneven load distribution in this condition. Keywords: electronic weighbridge, load cell, eccentricity, error.